2005
DOI: 10.1097/01.mao.0000176172.87141.5d
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dynamics Shift of Vestibular Evoked Myogenic Potentials in Patients with Endolymphatic Hydrops

Abstract: The peak amplitude of vestibular evoked myogenic potentials in the endolymphatic hydrops group was at a higher frequency than in the control group. The frequency of the saccule (nu) should be proportional to radical(tau/sigma), where tau is the tension of membrane and sigma is its density. We advocate the hypothesis that the shift in frequency dynamics of vestibular evoked myogenic potential in patients with endolymphatic hydrops originates from the morphologic features of the saccule, analogous to an expanded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 14 publications
2
34
1
1
Order By: Relevance
“…In Ménière's disease, two major changes in cVEMP were seen as a result of possible lesions of the otolith organs: an elevated threshold and altered tuning [Rauch et al, 2004;Node et al, 2005;Lin et al, 2006;Kim-Lee et al, 2009]. As reported before, healthy subjects showed the best response (highest amplitude and lowest threshold) for cVEMP induced by an AC stimulus at a stimulus frequency of approximately 500 Hz.…”
Section: Frequency Dependence Of Vemp In Ménière's Diseasementioning
confidence: 59%
See 1 more Smart Citation
“…In Ménière's disease, two major changes in cVEMP were seen as a result of possible lesions of the otolith organs: an elevated threshold and altered tuning [Rauch et al, 2004;Node et al, 2005;Lin et al, 2006;Kim-Lee et al, 2009]. As reported before, healthy subjects showed the best response (highest amplitude and lowest threshold) for cVEMP induced by an AC stimulus at a stimulus frequency of approximately 500 Hz.…”
Section: Frequency Dependence Of Vemp In Ménière's Diseasementioning
confidence: 59%
“…It has been shown that AC sound is easy to use in a clinical setting and the stimulus characteristics can be controlled; for example, the duration, level and frequency of the stimulus can be easily changed. However, in most studies, solely one AC stimulus frequency, generally 500 Hz, was used for testing VEMP because this particular stimulus frequency was proven to be the most effective in evoking VEMP [Todd et Frequency Tuning of oVEMP in Normal Subjects and Ménière's Disease Audiol Neurotol 2012;17:12-19 13 al., 2000; Welgampola and Colebatch, 2001;Rauch et al, 2004;Node et al, 2005;Chihara et al, 2009a;Kim-Lee et al, 2009;Todd et al, 2009;Park et al, 2010].…”
Section: General Introduction To Vestibular Evoked Myogenic Potentialsmentioning
confidence: 99%
“…However, this 'best' frequency can lie between 500 and 1000 Hz 22 or between 500 and 700 Hz. 23 The alteration in tuning and threshold shift in Mé niè re's disease has been attributed to the presumed hydropic distension of the saccule. 23 In this study, T vestibular evoked myogenic potential was 116 + 7.7 dBSPL.…”
Section: Discussionmentioning
confidence: 99%
“…23 The alteration in tuning and threshold shift in Mé niè re's disease has been attributed to the presumed hydropic distension of the saccule. 23 In this study, T vestibular evoked myogenic potential was 116 + 7.7 dBSPL. The threshold vestibular evoked myogenic potential response in healthy adults ranges between 110 19 and 114.4 dBSPL.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo a la anatomía del laberinto, la EM podría afectar inicialmente a la parte más inferior (cóclea y sáculo), para ascender posteriormente hacia el utrículo y los CS [44]. También es posible que se produzca un cambio de sintonización, de manera que la mejor respuesta con VEMP por VA no sea a 500 Hz sino a 1 kHz [45], sugiriéndose incluso, que la relación de amplitudes entre 500 / 1000 Hz sería un fiel indicador de la enfermedad. En definitiva, los diversos hallazgos podrían deberse a diferentes estadios del proceso, a la influencia de las crisis agudas y a la actividad fluctuante de la enfermedad [5].…”
Section: Enfermedad De Ménière (Em)unclassified